2021
DOI: 10.1108/apjba-11-2019-0230
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness of celebrity and product match-up for two high consumer involvement situations

Abstract: PurposeThe study attempted to gauge the relative effectiveness of celebrity and product image match-up in comparison to non-celebrity attractive endorsers for two distinct high involvement situations. Also, due to the expected demographic diversity among target consumers, the study aimed at assessing the impact of respondent's age and gender on the effectiveness of image match-up.Design/methodology/approachBuilding on the three-order hierarchy model, two experiments were conducted (utilising celebrity and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…AI is a new, developing, and advanced technology. The adoption of new technologies is slowed by the fact that the average person may not fully comprehend how the technology operates (Hussain et al, 2021). Higher perceived risk is often caused by time, money, and emotional loss due to the failure of AI voice assistant services.…”
Section: Discussionmentioning
confidence: 99%
“…AI is a new, developing, and advanced technology. The adoption of new technologies is slowed by the fact that the average person may not fully comprehend how the technology operates (Hussain et al, 2021). Higher perceived risk is often caused by time, money, and emotional loss due to the failure of AI voice assistant services.…”
Section: Discussionmentioning
confidence: 99%
“…A main determinant of effectiveness of celebrity endorsement is congruence between product and the endorser (Moharana et al, 2023). Hussain et al (2021) claimed that the academic view of 'match-up' is reliable with assumptions of earlier researches that have focused on the congruence based effectiveness. They submitted that the appropriate congruence between endorsed brand and celebrity will lead to effective celebrity endorsement.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Dowling (1988) has defined source credibility as the believability of the perceptions of a company by a certain source, usually an earlier employee of the company. Source credibility has also been referred to as the perceived trustworthiness and credibility of the source (Hadinejad et al, 2022;Hussain et al, 2021;Roy et al, 2013). Tham et al (2013) identified three different sources of messages that other people may use as bases for their choices and preferences for a specific action, such as the decision to go to a tourist destination or apply for a job in a company, depending on how credible the sources are: organic, induced and real.…”
Section: Employee Attractiveness and Youth Employmentmentioning
confidence: 99%